Evan’s Index in adult Nepalese population: A Computerized Tomographic Study - Shrestha, Pragya; Mansur, Dil Islam; Karki, Subindra; Maskey, Sunima; Sah, Bishal; Chaudhary, Roshan (Birat Journal of Health Sciences, 2022)
Introduction: Evan's Index is a linear measurement of the ventricular size which is used as an indirect marker of ventricular volume. It is used widely as a screening tool to rule out ventricular enlargement. As the ventricular enlargement indicates the neuropathological state of the brain, Evan's Index serves as the quick and reliable method to assess ventricular size. Objectives: The study aims to generate a baseline value of Evan's Index among the Nepalese population and also investigates the effect of age and gender on EI. Methodology: A quantitative study was conducted in the Department of Anatomy, Kathmandu University School of Medical Sciences and data was collected from the Department of Radiodiagnosis, Dhulikhel Hospital, Kathmandu University Hospital. The study was done on 385 head CT Scans of the individuals of mean age of 45.44years. The ratio of inter anterior horns distance of the lateral ventricles and maximal internal diameter of the skull at the same level was taken to calculate Evan’s Index. Results: The mean value of Evan’s index in the present study was 0.250.03. The study did not report gender-wise variation in Evan's Index (p>0.05). Evan’s index was minimum at the age group of 20-29 and maximum at the age group of 80-89. The value of Evan’s Index showed a significant increase with the age (p<0.05). Conclusions: The study provides the mean value of Evan’s Index among the Nepalese population. Even though Evan’s Index is not influenced by gender, the value increases with normal aging.